POESÍA Y TEATRO. ERATÓ Y CALÍOPE EN LA CASA DE MELPÓMENE Y TALÍA: POETRY AND THEATER. ERATO AND CALLIOPE IN THE HOUSE OF MELPOMENE AND THALIA - LÓPEZ MOZO, Jerónimo (Signa: Revista de la Asociación Española de Semiótica, 2024)
El teatro y la poesía siempre han ido de la mano y juntos seguirán durante largo tiempo, aunque el matrimonio verso y teatro se ha roto, a la vista de la escasa presencia de aquél en los textos dramáticos actuales. En este trabajo, que se une a lo expuesto en el trigésimo seminario internacional del SELITEN@T, se realiza un panorama sobre las relaciones del teatro con la poesía en el siglo XX y especialmente en el XXI. Abstract: Theater and poetry have always gone in hand and will continue together for a long time, although the marriage of verse and theater has broken down, in view of its scarce presence in current dramatic texts. In this work, which joins what exposed in the thirtieth international seminar of SELITEN@T, an overview of the relations between theater and poetry in the 20th and particularly the 21st centuries. Keywords: Theater. Poetry. Spain. 20th Century. 21st Century.